First Movers on Sustainable Banking" Global Basis Sustainable Finance Concept: Sharia Finance Period 2018-2020 Sector Performance Reporting Initiative (GRI) - Ridwansyah (International Journal of Educational Research Excellence, 2023)
The idea of sustainable finance is becoming more and more important in today’s fast-paced global world, pushing financial institutions to take the effects on the environment, society, and economy into account when conducting business. The primary resource for reporting sustainable performance is the Global Reporting Initiative (GRI). Nevertheless, there are still few comprehensive studies on the application of BRI Syariah and Bank Muamalat’s sustainable finance concept in the context of the sharia financial sector, particularly when it comes to evaluating the sector’s performance from 2018 to 2020. The research question is: What impact does the sharia financial sector’s performance have from the application of the concept of sustainable finance, as defined by "first movers on sustainable banking" and based on the Global Reporting Initiative (GRI)? and what and what is the impact of implementing the sustainable finance concept "first movers on sustainable banking" based on the Global Reporting Initiative (GRI) on the performance of the sharia financial sector ? . This kind of research is classified as qualitative, and it is specifically descriptive in nature. A secondary source is the data source that was used. Time triangulation, literature analysis, and documentation are some of the methods used in data collection. After that, the data was examined through data reduction, data visualization, and conclusion-making. Based on GRI guidelines, BRI Syariah has successfully implemented sustainable financial concepts with satisfactory economic performance, including market adaptation and moderate growth. Actions taken in the field of green banking, like funding TJSL, CSR, and sustainable agriculture as well as renewable energy, benefit society. In the areas of the economy, environment, and society, Bank Muamalat Indonesia has also been successful in putting the GRI sustainable finance concept into practice. Liquidity, fund raising, and efficient asset management all demonstrate its financial sustainability.